2023
DOI: 10.1097/md.0000000000035122
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the oncogenic and immunological role of SPON2 in human tumors

Jiali Tang,
Qing Huang,
Xuanwen Li
et al.

Abstract: Background: Sapiens spondin-2 (SPON2) is a protein found in the extracellular matrix that plays a role in a number of processes, including immune reactions and cell adhesion, and is closely linked to the emergence of a number of tumor types. However, we know very little about Sapiens spondin-2. Therefore, we performed a systematic pan-carcinogenic analysis to explore the relationship between Sapiens spondin-2 and cancers. Materials and methods: By compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Some components of the extracellular matrix can affect the recruitment of monocytes/macrophages [ 115 , 116 ]. Spondin 2 (SPON2), a matricellular protein 2, is essential for recruiting lymphocytes and initiating immune responses, as well as having a role in tumor progression [ 117 , 118 ]. Recent studies have shown that SPON2 expression is positively correlated with M2-TAM infiltration in clinical CRC tumors and with poor prognosis of patients.…”
Section: Re-education Of Tam Towards the Anti-tumor Phenotypementioning
confidence: 99%
“…Some components of the extracellular matrix can affect the recruitment of monocytes/macrophages [ 115 , 116 ]. Spondin 2 (SPON2), a matricellular protein 2, is essential for recruiting lymphocytes and initiating immune responses, as well as having a role in tumor progression [ 117 , 118 ]. Recent studies have shown that SPON2 expression is positively correlated with M2-TAM infiltration in clinical CRC tumors and with poor prognosis of patients.…”
Section: Re-education Of Tam Towards the Anti-tumor Phenotypementioning
confidence: 99%